2010
DOI: 10.5194/acpd-10-11513-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High variability of the heterogeneous ice nucleation potential of oxalic acid dihydrate and sodium oxalate

Abstract: The heterogeneous ice nucleation potential of airborne oxalic acid dihydrate and sodium oxalate particles in the deposition and condensation mode has been investigated by controlled expansion cooling cycles in the AIDA aerosol and cloud chamber of the Karlsruhe Institute of Technology at temperatures between 244 and 228 K. Previous laboratory studies have highlighted the particular role of oxalic acid dihydrate as the only species amongst a variety of other investigated dicarboxylic acids to be capable of acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The fact that cooling to a temperature of 244 K is sufficient to preactivate the oxalic acid dihydrate particles sheds a new light on the interpretation of our previous AIDA experiments, where a high deposition mode ice nucleation ability was found for particles that had been injected and crystallized at 244 K and then been probed in an expansion cooling cycle at that temperature [ Wagner et al , ]. In view of the results from the new temperature cycling experiment, crystallization at 244 K directly yields a population of preactivated organic crystals with frozen aqueous solution pockets.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The fact that cooling to a temperature of 244 K is sufficient to preactivate the oxalic acid dihydrate particles sheds a new light on the interpretation of our previous AIDA experiments, where a high deposition mode ice nucleation ability was found for particles that had been injected and crystallized at 244 K and then been probed in an expansion cooling cycle at that temperature [ Wagner et al , ]. In view of the results from the new temperature cycling experiment, crystallization at 244 K directly yields a population of preactivated organic crystals with frozen aqueous solution pockets.…”
Section: Resultsmentioning
confidence: 80%
“…For the oxalic acid experiments, the initial AIDA temperature has to be higher than in the experiments with succinic acid. In a previous AIDA study, oxalic acid solution droplets that crystallized at 244 K were found to be highly ice active in the deposition mode at that temperature [ Wagner et al , ]. As proven by infrared extinction spectroscopy, the injected solution droplets crystallized as oxalic acid dihydrate.…”
Section: Resultsmentioning
confidence: 90%
“…A key question of the recent studies was the identification of organic compounds that are able to contribute to the abundance of ice-nucleating particles (INPs) in the atmosphere, i.e., particles that are responsible for heterogeneous ice nucleation [Vali et al, 2015]. Some organic compounds, like various monocarboxylic and dicarboxylic acids, exist in the crystalline solid state and were shown to promote heterogeneous ice nucleation via deposition nucleation when prevalent as bare substances [Baustian et al, 2010;Schill and Tolbert, 2012;Shilling et al, 2006;Wagner et al, 2010] or via immersion freezing when embedded as crystalline inclusions in water or aqueous solution droplets [Wagner et al, 2011[Wagner et al, , 2015Zobrist et al, 2006]. Organic compounds also frequently form amorphous semisolid or amorphous solid (glassy) states at low temperature and/or relative humidity [Koop et al, 2011;Virtanen et al, 2010;Zobrist et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Some organic compounds, like various monocarboxylic and dicarboxylic acids, exist in the crystalline solid state and were shown to promote heterogeneous ice nucleation via deposition nucleation when prevalent as bare substances [ Baustian et al ., ; Schill and Tolbert , ; Shilling et al ., ; Wagner et al ., ] or via immersion freezing when embedded as crystalline inclusions in water or aqueous solution droplets [ Wagner et al ., , ; Zobrist et al ., ]. Organic compounds also frequently form amorphous semisolid or amorphous solid (glassy) states at low temperature and/or relative humidity [ Koop et al ., ; Virtanen et al ., ; Zobrist et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The high ice nucleation ability of NaCl • 2H 2 O might represent an example for the chemical bond requirement in heterogeneous ice nucleation [Pruppacher and Klett, 1997], meaning that the water molecules in the crystal are preferential sites for the further deposition of water vapor from the gas phase. Also a chemically different hydrate species, namely oxalic acid dihydrate, has recently been observed to be a partly very efficient ice nucleus in the deposition mode [Kanji et al, 2008;Wagner et al, 2010]. Additionally, the microscope images recorded by Wise et al [2012] show that the dihydrate particles have a higher degree of surface roughness compared to the anhydrous crystals which is another factor that could add to the particular ice nucleation efficiency of NaCl • 2H 2 O.…”
Section: Introductionmentioning
confidence: 99%